Mid-century modern design : a complete sourcebook - Bradbury, Dominic (Thames & Hudson, 2020)
Essential reading for all collectors and design aficionados, this book is the ultimate survey of mid- century modern design and architecture now available in a sleek, compact form. A definitive survey of mid-century modern design and architecture in an accessible compact edition, this book offers a rich overview of one of the most popular, collectable, and dynamic periods of design. With rich and diverse examples of everything from furniture and lighting to ceramics and textiles to graphics and posters to interior design and architecture, this sleek compendium of mid-century style includes over 1,000 illustrations representing classic designs and little-seen rarities, as well as entries on nearly 100 major creators, such as Dieter Rams, Robin Day, Isamu Noguchi, Lucie Rie, Charles and Ray Eames, Alvar Aalto, and Oscar Niemeyer. An additional illustrated dictionary features hundreds more influential mid-century designers, manufacturers, organizations, schools, and movements.